Protective Efficacy of an mRNA Vaccine Against HP-PRRSV Challenge in Piglets - Jiaqi Liu; Shiting Ni; Yaning Lv; Ze Tong; Pingxuan Liu; Xin Zong; Guosheng Chen; Yan Zeng; Chenchen Wang; Chen Tan (Microorganisms, 2025)
The global pork production sector continues to experience substantial financial burdens attributable to porcine reproductive and respiratory syndrome virus (PRRSV) infections. Despite the current epidemiological landscape in which NADC30-like strains predominate alongside cocirculating diverse PRRSV subtypes, highly pathogenic PRRSV (HP-PRRSV) remains a persistent threat. Furthermore, currently available commercial PRRS vaccine formulations exhibit restricted heterologous protection efficacy. The development of novel mRNA-based vaccines represents a promising strategy for PRRS mitigation protocols. In response to these epidemiological challenges, an HP-PRRSV strain (Lineage 8), designated as JX021, was isolated and characterized in this study. Pathogenicity experiments confirmed that JX021 induces severe clinical symptoms in piglets. Moreover, by combining immunoinformatics and literature-guided approaches, critical antigenic epitopes on HP-PRRSV (represented by the JXA1 strain) structural proteins were identified, enabling the design and synthesis of a multiepitope mRNA vaccine. The survival of piglets immunized with the mRNA vaccine was higher than that of the inactivated vaccine immunization group and the PBS group. Compared with the inactivated vaccine group, the mRNA vaccine group presented reductions in viremia and lung lesions. These findings provide new insights into the design and development of further PRRS vaccine research.